Problem and promise in Colin E. Gunton's doctrine of creation - Whitney, William B. (Studies in Reformed Theology, 2013)
While much dialogue has focused on aspects of Colin Gunton's Trinitarian theology, there has been a need for a full-scale study of Gunton's doctrine of creation that locates the significance of his understanding of creation within the wider spectrum of his theology. Problem and Promise demonstrates how Gunton's doctrine of creation cannot be read in abstraction from his Trinitarian theology and argues that creation remains a central feature in Gunton's writing that holds lasting importance for understanding ethical and moral aspects of Gunton's theology. William B. Whitney establishes how this Trinitarian account of creation goes beyond offering a theological description of the created realm and also provides the basis for understanding human involvement in creation through the enterprises of culture.